Spatial Analysis of Land Cover Changes on Obi Island, Indonesia due to Nickel Mining Activities - Wlary, Anelia P.; Purwantara, Suhandi; Rakuasa, Heinrich; Khromykh, Vadim V. (Jurnal Sumberdaya Alam dan Lingkungan, 2025)
Obi Island in North Maluku Province, Indonesia, has undergone significant land cover changes due to the expansion of nickel mining activities, especially since official operations began in 2010; the conversion of built-up land and vegetated areas into mining and settlement zones has increased pressure on land carrying capacity and contributed to more frequent flooding during the rainy season. This study uses spatial analysis based on Landsat 5 (1995) and Landsat 8 OLI (2025) satellite imagery to map land cover changes over three decades. The results show an increase in built-up land area from 448.84 hectares to 698.67 hectares, as well as the emergence of a 4,963.67-hectare mining area in 2025, while open land, water bodies, and vegetation have significantly declined. These findings demonstrate the direct impact of mining activities on landscape dynamics and the local environment, necessitating sustainable management and mitigation measures to maintain ecological balance and reduce the risk of related disasters.Keywords: LULC, Nickel Mining, Obi island